FORMATION AND DEVELOPMENT OF UKRAINIAN INSTITUTE OF ADVOCACY IN TIMES OF KIEVAN RUS AND DURING THE POLISH-LITHUANIAN BOARD - Заборовский, Виктор Викторович (Teisė, 2016)
Analysis of the formation of Ukrainian institute of advocacy in the days of Kievan Rus in the period of the Polish-Lithuanian rule. The conclusion is that the of Ukrainian institute of advocacy was born in the times of Kievan Rus, but at this stage of the activity of the defender does not contain signs of a professional nature. The origin of professional advocacy in Ukraine comes at a later stage of its development, namely in the period of the Polish-Lithuanian rule. That is the conclusion gives us the opportunity to reach an analysis of the Statutes of the Grand Duchy of Lithuania, in particular the third edition in 1588, as a profession already procurator acquires the features of a professional activity.